Microplastic toxicity: mechanisms, assessment methods, and future research directions - Zhang, Yifan; Ren, Jiale; Zheng, Binying; Sun, Jiefang; Zhang, Jing; Niu, Yumin; Shao, Bing; Jin, Yushen (Frontiers in Toxicology, 2026)
Microplastics (MPs), plastic particles under 5 mm in diameter, represent a pervasive and persistent global environmental contaminant with cascading adverse effects on aquatic/terrestrial organisms and human health. While existing reviews have summarized isolated aspects of MP toxicity or assessment methods, this review advances the field through three integrated contributions that address critical knowledge gaps. First, it synthesizes physical, chemical, and biological toxicity mechanisms into a unified “particle-environment-organism” cascade, highlighting synergistic interactions that are often overlooked in fragmented syntheses. Second, it provides a critical evaluation of methodological advances by proposing a standardized dosing framework designed to address longstanding challenges to cross-study comparison. Third, it bridges ecological and human toxicology via an integrative conceptual model linking MP properties, environmental modifiers, biological modulating factors, key toxicological events (KTEs) and adverse outcomes, while outlining actionable research priorities and regulatory strategies. By consolidating these elements, this review synthesizes current understanding of MP toxicity and provides a structured framework to enhance comparability across studies, as well as guide future research and regulation. Crucially, it aims to narrow the gap between lab-based findings and real-world application, facilitating the translation of scientific insights into practical strategies for mitigating risks to both ecosystems and human health.